2011
DOI: 10.1111/j.1751-0813.2011.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma in a woma python (Aspidites ramsayi)

Abstract: Osteosarcoma of the axial skeleton in an 18-month-old woma python (Aspidites ramsayi) is described. A subcutaneous mass overlying the costal arches enlarged progressively over a period of 5 months and, in that time, became ulcerated and more invasive of surrounding tissues. A punch biopsy of the lesion under general anaesthesia provided tissue for histopathology and diagnosis of low-grade osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
9
0
3
Order By: Relevance
“…Bone tumours in snakes and lizards are described as masses with a mixed lytic and productive radiographic appearance (Schonbauer and others 1982, Hernandez-Divers and Garner 2003, Garner and others 2004, Gál and others 2007, Cowan and others 2011). …”
Section: Diagnostic Imaging Modalitiesmentioning
confidence: 99%
“…Bone tumours in snakes and lizards are described as masses with a mixed lytic and productive radiographic appearance (Schonbauer and others 1982, Hernandez-Divers and Garner 2003, Garner and others 2004, Gál and others 2007, Cowan and others 2011). …”
Section: Diagnostic Imaging Modalitiesmentioning
confidence: 99%
“…Three retrospective studies examining 100 years of reptile necropsy results at zoological institutions found that neoplasia had become more frequently diagnosed over this time period . Improved husbandry and subsequent increased life span, improved diagnostics and increased numbers in the captive population have been suggested as contributing factors …”
Section: Discussionmentioning
confidence: 99%
“…Neoplasia is rarely reported in reptiles. In this case report and clinical review, an 18‐month‐old woma python was presented with a discrete mass 8 . The snake behaved normally, was fed bimonthly, and defecated regularly.…”
Section: Wildlife and Zoosmentioning
confidence: 93%